Length-weight relationship and condition factor of Malaysian Mahseer (Tor sp.) from selected wild and cultured populations across Peninsular Malaysia - Noor Haliza Mohamed Ibrahim; Nur Farhana Mohd Yusoff; Mohd Shafiq Zakeyuddin; Shahril Mod Husin; Simon Kumar Das; Shukor Md Nor; Shairah Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2025)
Biometric data is essential for effective fisheries management, particularly for the Malaysian mahseer (Tor sp.), a potential aquaculture species currently listed as ‘Data Deficient’. Wild populations are declining due to habitat degradation, while current aquaculture practices fall short of meeting market demand. This study investigates the length-weight relationship (LWR) and condition factor (K) of Malaysian mahseer populations, with samples categorized by origin (wild: n=25; cultured fish: n=29) based on their respective sampling locations. Wild fish ranged from 12.00 to 46.00 cm in length and 22.00 to 1060.00 g in weight, while cultured fish ranged from 15.30 to 41.30 cm in length and 63.71 to 559.22 g in weight. Separate LWR regression analyses showed hypoallometric growth in both populations (bwild = 2.614, bcultured = 1.779), with wild fish exhibiting stronger length-weight correlations (R² = 0.96) compared to cultured fish (R² = 0.52). The K-values were higher in the cultured population (Kcultured = 1.891 vs Kwild = 1.203), highlighting the controlled environment’s positive influence on growth. By distinguishing the biometric characteristics of wild and cultured populations, this study provides critical insights for enhancing aquaculture practices and conserving wild mahseer populations in Peninsular Malaysia.